2008
DOI: 10.1128/ec.00011-08
|View full text |Cite
|
Sign up to set email alerts
|

High Resistance to Oxidative Stress in the Fungal Pathogen Candida glabrata Is Mediated by a Single Catalase, Cta1p, and Is Controlled by the Transcription Factors Yap1p, Skn7p, Msn2p, and Msn4p

Abstract: We characterized the oxidative stress response of Candida glabrata to better understand the virulence of this fungal pathogen. C. glabrata could withstand higher concentrations of H 2 O 2 than Saccharomyces cerevisiae and even Candida albicans. Stationary-phase cells were extremely resistant to oxidative stress, and this resistance was dependent on the concerted roles of stress-related transcription factors Yap1p, Skn7p, and Msn4p. We showed that growing cells of C. glabrata were able to adapt to high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
123
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 77 publications
15
123
0
1
Order By: Relevance
“…This rescue of the virulence phenotype has been observed for another C. glabrata mutant we have identified (A. Taravaud, J. Bourdeaux, and D. Ferrandon, unpublished observations). It will be interesting to determine whether the C. glabrata catalase is required for the pathogen to withstand the cellular immune response, because it is currently unknown whether Drosophila hemocytes produce an oxidative shock to kill ingested microbes (56). The existence of an oxidative burst can also be tested on the host side by reducing genetically the expression of the Dual oxidase gene or that of the NADPH oxidase gene in hemocytes.…”
Section: Glabrata Persist Even In Wild-type Fliesmentioning
confidence: 99%
“…This rescue of the virulence phenotype has been observed for another C. glabrata mutant we have identified (A. Taravaud, J. Bourdeaux, and D. Ferrandon, unpublished observations). It will be interesting to determine whether the C. glabrata catalase is required for the pathogen to withstand the cellular immune response, because it is currently unknown whether Drosophila hemocytes produce an oxidative shock to kill ingested microbes (56). The existence of an oxidative burst can also be tested on the host side by reducing genetically the expression of the Dual oxidase gene or that of the NADPH oxidase gene in hemocytes.…”
Section: Glabrata Persist Even In Wild-type Fliesmentioning
confidence: 99%
“…Accordingly, an inactivation of these detoxifying enzymes leads to severe loss in virulence and viability inside immune cells (59). The oxidative stress response of C. glabrata is controlled by the transcription factors Yap1, Skn7, Msn2, and Msn4 (30,60,61), which mediate resistance of C. glabrata to H 2 O 2 and other oxidants. Additionally, C. glabrata possesses a catalase (Cta1p) that is required to survive oxidative stress (although this is dispensable in a mouse model of systemic infection) (60,62).…”
Section: Glabrata Cells Repress the Production Of High Ros Levelsmentioning
confidence: 99%
“…The oxidative stress response of C. glabrata is controlled by the transcription factors Yap1, Skn7, Msn2, and Msn4 (30,60,61), which mediate resistance of C. glabrata to H 2 O 2 and other oxidants. Additionally, C. glabrata possesses a catalase (Cta1p) that is required to survive oxidative stress (although this is dispensable in a mouse model of systemic infection) (60,62). In agreement with a previous study, which showed that C. glabrata can suppress the release of oxidants during its interaction with a murine macrophage cell line (21), in this study we demonstrate repression of ROS production by primary human macrophages.…”
Section: Glabrata Cells Repress the Production Of High Ros Levelsmentioning
confidence: 99%
“…exhibit unequal oxidative stress resistances in vitro [20][21][22] , and different in vitro virulence potentials 23 , and we proposed that this may contribute to the capacity of each species to cause candidemia 22 . Taking into account these differences, total glutathione levels and the cellular TAC were assessed in 8 Candida species.…”
Section: Introductionmentioning
confidence: 99%